Improving Students’ Vocabulary Mastery and Listening Skill by Using English Religious Song Lyric at Postulancy - Indonesia - Sondang Manik; Lina Sriulina Br. Tarigan (JETAL: Journal of English Teaching & Applied Linguistic, 2023)
This research aims to investigate whether the use of English religious song lyric improve students’ vocabulary mastery and listening skill at Postulancy-Indonesia. The research was designed by implementing a Classroom Action Research (CAR). This study used Quantitative and Qualitative data. The finding indicates that English religious song lyric improved students’ vocabulary mastery and listening skill. The improvement can be proved by the Mean of the students’ score from Pre-Test up to Post-Test 2. In vocabulary mastery, the Mean of students’ Pre-Test was 43.92, but then after implementing the English religious song lyric, the students’ score improved in Cycle-1 with the Mean was 66.56 and in Cycle-2 with the Mean was 90.04. In addition, it was found the data that 100% students passed the KKM in vocabulary mastery in Cycle-2. In listening skill, the Mean of students’ Pre-Test was 29.04, but then after implementing the English religious song lyric, the students’ score improved in Cycle-1 with the Mean was 58.24 and in Cycle-2 with the Mean was 76.56. In addition, it was found the data that only 67% students passed the KKM in listening skill in Cycle-2. Based on data, it can be concluded that the students’ vocabulary mastery was improved significantly by using English religious song lyric. Furthermore, the students’ improvement was not only shown by the Mean of students’ score but also by the students’ motivation or interest in studying which was increasing in Cycle-1 and Cycle-2. It can also be concluded that English religious song lyric is a good media (recommended) in teaching vocabulary mastery and listening skill. Key words: Vocabulary Mastery, Listening Skill, Song Lyric, Postulancy